Wavevector- and frequency-dependent shear viscosity of water: the modified collective mode approach and molecular dynamics calculations - Omelyan, I.P.; Mryglod, I.M.; Tokarchuk, M.V. (Condensed Matter Physics, 2005)
The transverse momentum time autocorrelation functions and wavevectorand
frequency-dependent shear viscosity are calculated for an interaction
site model of water using a modified collective mode approach and
molecular dynamics simulations. The modified mode approach is based
on a formulation which consistently takes into account non-Markovian effects
into the kinetic memory kernels. As is demonstrated by comparing
the theory results with the molecular dynamics data, the entire frequency
dependence of the shear viscosity can be reproduced quantitatively over
the whole wavelength range in terms of six generalized collective modes
employing the kinetic memory kernel in the non-Markovian approximation
of the third order. It is also shown that the results corresponding to the exact
atomic and abbreviated molecular descriptions may differ considerably.
In the infinite wavevector regime the dynamic correlations are completely
determined by a single free motion of the molecules. Часові кореляційні функції, що відповідають флуктуаціям поперечного імпульсу, та зсувна в’язкість, залежна від хвильового вектора та частоти, обчислюються для моделі води використовуючи модифікований підхід колективних мод та метод молекулярної динаміки. Модифікований підхід базується на більш загальному формулюванні, яке послідовно враховує немарківські ефекти у кінетичних ядрах пам’яті. Порівнюючи теоретичні результати з даними молекулярної динаміки продемонстровано, що частотна залежність зсувної в’язкості може бути кількісно відтворена в усій області хвильових векторів за допомогою шести узагальнених колективних мод і кінетичного ядра пам’яті в немарківському наближенні третього порядку точності. Показано також, що результати, які відповідають точному атомному і скороченому молекулярному описам, можуть відрізнятися суттєво. У границі нескінченних значень хвильового вектора динамічні кореляції повністю визначаються вільним рухом молекул.